Pelatihan Pemanfaatan Labu Kuning Sebagai Peluang Bisnis Kelurahan Malasilen Kota Sorong - Sofia, Susetyowati; Rokhimah; Wahyuni, Tri; Azizzah, Citra Nur; Mau, Irma Handayani; Harniati, Sara (PT. Karya Inovatif Nusantara, 2024)
Community Service (PKM) with the theme Training on the Use of Yellow Pumpkin as a Business Opportunity for Housewives in Malasilen Village, Sorong City. The partners for this activity are the women residents of Jl. Bima Complex Behind KM.10 Malasilen Village. The activity was held for one day on Saturday, May 4 2024 and was attended by 13 (thirteen) local residents. The aim of this activity is to provide training on the use of abundant pumpkin and provide creativity and innovation that is more valuable and can later be used as a business opportunity. The methods used in this activity are: Observation, Licensing, Activity Preparation, Implementation Activities, Evaluation, Final Report. Providing business ideas for housewives in optimizing abundant natural resources, especially pumpkin, so that it becomes an innovative pumpkin sponge product. Apart from that, we hope that this activity can motivate housewives to have business opportunities so that they can increase their income.